1996
DOI: 10.1523/jneurosci.16-17-05334.1996
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Potentiation in Distinct Subtypes of Hippocampal Nonpyramidal Neurons

Abstract: We have investigated NMDA receptor-dependent long-term potentiation (LTP) in distinct subtypes of nonpyramidal neurons of the CA1 hippocampus using induction protocols that permitted the differentiation between a direct form of LTP and plasticity resulting simply from the "passive propagation" of LTP occurring on CA1 pyramidal neurons. Two types of stratum (st.) oriens/ alveus interneurons received passive propagation of synaptic potentiation via the recurrent collaterals of CA1 pyramidal cells, but neither su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
130
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(145 citation statements)
references
References 64 publications
15
130
0
Order By: Relevance
“…radiatum, spiny dendrites located in strata radiatum and lacunosum-moleculare, and its axon projecting to str. oriens (Maccaferri and McBain, 1996) revealed sIPSC kinetics similar to those found in pyramidal cells (Table 1) but with a smaller average amplitude (20.7 pA).…”
Section: Differences In Sipsc Properties Between Pyramidal Cells and supporting
confidence: 69%
See 1 more Smart Citation
“…radiatum, spiny dendrites located in strata radiatum and lacunosum-moleculare, and its axon projecting to str. oriens (Maccaferri and McBain, 1996) revealed sIPSC kinetics similar to those found in pyramidal cells (Table 1) but with a smaller average amplitude (20.7 pA).…”
Section: Differences In Sipsc Properties Between Pyramidal Cells and supporting
confidence: 69%
“…Recent in vitro and in vivo studies using intracellular labeling methods have identified several hippocampal CA1 interneuron types and have classified them according to their input and output features (Buhl et al, 1994;McBain et al, 1994;Sik et al, 1995;Freund and Buzsáki, 1996;Halasy et al, 1996;Maccaferri and McBain, 1996). Numerous physiological recordings were obtained from interneurons in this hippocampal subfield, but only two groups of dendritic inhibitory cells, namely bistratified cells and O-LM cells (Buhl et al, 1994;McBain et al, 1994;Sik et al, 1995;Halasy et al, 1996), have been morphologically characterized in detail.…”
Section: Novel Type Of Hippocampal Ca1 Interneurons With Axonal Arbormentioning
confidence: 99%
“…First, electrical stimulation of RE -CA1 afferents at their origin causes an active (subthreshold) depolarization of the apical dendrites of pyramidal cells, which may enhance their state of excitability. Second, RE-elicited spiking of extracellularly recorded units was not detected in the stratum pyramidale but in strata oriens/alveus and radiatum, which indicates synaptic excitation of local nonpyramidal cells that are likely associated with inhibitory mechanisms (Lacaille et al, 1987;Samulack et al, 1993;McBain et al, 1994;Steffensen, 1995;Bergles et al, 1996;Maccaferri and McBain, 1996; for review, see Freund and Buzsáki, 1996). Furthermore, evidence is provided for the existence of a projection from caudal to rostral RE that is considered to form the anatomical substrate underlying the presently observed disynaptic and complex RE-evoked responses in CA1.…”
Section: Discussionmentioning
confidence: 92%
“…According to their distinctive morphologies, axonal targets, and neurochemical markers, CA1 interneurons in strata oriens/ alveus and radiatum represent a heterogeneous class of nonpyramidal cells (McBain et al, 1994;Buckmaster and Soltesz, 1996;Freund and Buzsáki, 1996;Maccaferri and McBain, 1996). A Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic inhibitory interneurons in the hippocampus may also control long-term modifications of synaptic strength induced by synaptic transmission (Buzsaki et al 1996;Maccaferri and McBain 1996;Miles et al 1996;Tsubokawa and Ross 1996;McMahon and Kauer 1997;Laezza et al 1999). …”
Section: Functions Of Gabaergic Interneurons In the Cortex And In Thementioning
confidence: 99%